A conserved editing mechanism for the fidelity of bacterial cell wall biosynthesis - Shambhavi Garde; Harikrishnan Selvaraj; Aakash Chandramouli; Gundlapally S. Reddy; Devesh Bahety; Pavan Kumar Chodisetti; Siddhesh S. Kamat; Manjula Reddy (Proceedings of the National Academy of Sciences, 2025)
Peptidoglycan (PG), a defining feature of the bacterial cell envelope, is crucial for cell integrity and morphology. PG is a macromolecular mesh consisting of glycan polymers crosslinked by short peptides encasing the cytoplasmic membrane. PG peptides contain two to five amino acids of both L- and D-configuration, with a conserved L-alanine residue at the first position in most bacteria. We previously identified a β-lactam hypersensitive mutant of Escherichia coli lacking yfiH (renamed pgeF ) that shows incorporation of L-serine or glycine instead of L-alanine. Here, we demonstrate that PgeF is an editing enzyme that imparts fidelity to the biosynthesis of PG peptides across bacterial genera. Using extensive mass spectrometry, we find accumulation of misincorporated cytoplasmic PG precursors in the absence of pgeF . Detailed biochemical analysis of several bacterial PgeF homologs reveals that PgeF specifically cleaves serine or glycine but not alanine from the PG precursors. Additionally, expression of heterologous ligases that incorporate L-serine or glycine is lethal in the absence of pgeF , indicating that L-alanine at the first position is crucial for wall integrity. Interestingly, PgeF is selectively conserved in bacteria and vertebrates; however, we find that the PG editing activity is exclusive to bacterial homologs. Furthermore, homologs from both taxa were previously characterized as purine nucleoside phosphorylases (PNP). Here, we find that they indeed have a weak PNP activity, but with no physiological relevance in bacterial systems. Overall, our study demonstrates the existence of a conserved proofreading pathway that is fundamental to the integrity of the bacterial cell wall.